Harnessing Natural Ingestive Behaviours of Dairy Animals for Improving their Productivity and Welfare (Indian Journal of Animal Production and Management, 2024)
The knowledge of ingestive behaviour of  cows and buffaloes is very important in improving  cow wellbeing and performance. The ingestive  behaviour of bovines has been classified into  sucking behaviour, feeding, rumination and water  drinking. Natural suckling performed for a total  duration of one hour daily on an average for 5-8  times in a day is of great importance for the proper  nourishment, health and welfare of calves.  Deprivation of suckling has detrimental effect both  of the mother and calves especially in native breeds  of cows and buffaloes. Feeding both grazing and  stall-feeding duration, frequency, the circadian  patterns of grazing and feeding determine the feed  intake and hence the production of the animals.  Similarly, rumination which completes the process  of feed ingestion, its duration, and frequency is  important for proper feed utilization and hence  animal performance. Length of manger space  available and partioning of manger for individual  cows helps reduce the competition at manger and  thus improves animal productivity. Availability,  temperature and quality of water for the drinking of  cows and buffaloes are the important  considerations for that improving water intake. This  paper reviews the available literature on the  ingestive behaviour especially of native cattle and  buffaloes and discusses how this knowledge can be  utilized for improving the production and welfare of  these animals.
Keywords: ingestive behaviour; dairy cattle; productivity; welfare